Pavement engineering : principles and practice - Mallick, Rajib B.; El-Korchi, Tahar (CRC Press, 2018)
"Pavement Engineering will cover the entire range of pavement construction, from soil preparation to structural design and life-cycle costing and analysis. It will link the concepts of mix and structural design, while also placing emphasis on pavement evaluation and rehabilitation techniques. State-of-the-art content will introduce the latest concepts and techniques, including ground-penetrating radar and seismic testing. This new edition will be fully updated, and add a new chapter on systems approaches to pavement engineering, with an emphasis on sustainability, as well as all new downloadable models and simulations."--Provided by publisher
Keywords: Pavements -- Design and construction.; elektronické knihy; electronic books